[R1’ = R1 - R2 & R2’ = R2 - R3]
[R1’ = R1 - R2]
[R2’ = R2*2]
[R2’ = R2 + R3]
= (1/2)[0 + 3(1 + q) - (1 + 6p + 3q) + p(6 + 3p - 3p)] [expansion by first row]
= (1/2)(3 + 3q - 1 - 6p - 3q + 6p) = 1
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation